﻿"Hate-Man Timon": A Study of Misanthropy in Shakespaare's Flays - Lisk, Ruth Maryann (My University, 1977)
In recent years it has been generally accepted that the difficulties in the text of Shakespeare's primarily from the fact that for some reason or other Shakespeare left the play unfinished. Although critics have advanced several theories, some biographical and some dramatic, to explain why Shakespeare might have abandoned the play, none of these explanations sufficiently considers the formidable problems surrounding the dramatic presentation of misanthropy. Because the unqualified hate is an emotion which most human beings find repugnant. it is difficult to present a genuine misanthrope as a sympathetic character. For this reason the most successful dramatic of misanthropy, such as Moliere's forester or Menander's, have aimed the audience the chance to ridicule the misanthrop's even while it sympathizes Nith some of his condemnations of humanity. This tendency was particularly intense in the early seventeenth century, when the story of Timon, the arch-misanthrope, was commonly used as a cautionary example of degenerate behaviour. Shakespeare• s problems would have been further increased by the fact that misanthropy finds expression chiefly through words rather than through deeds, and thus does not easily lend itself to a theatrical presentation. Because the misanthrope normally reveals his hatred of mankind in long tirades; and because his condition is not subject to change or development, there is always the danger that a play containing such a character will degenerate into a static series of abusive debates. This danger is especially prevalent then, as in the case of Shakespeare's Timon, the misanthrope becomes the central figure.
This thesis examines Shakespeare's depiction of misanthropy in the light of Elizabethan attitudes and practical stage considerations. In the first two chapters, I study sixteenth and early seventeenth century treatments of misanthropy and the Timon story in an effort to discover what preconceived ideas an Elizabethan audience might have brought to Shakespeare's play. I have discovered that a significant number of didactic writers vigorously condemned misanthropy, either as a beastly vice born of envy, or as a symptom of insanity. So intent were they on centering Timon's behaviour, that they frequently altered Plutarch's account of the Timon story to depict the arch-misanthrope as an active seeker after man's destruction. By contrast, the period's literary works tended to depict the misanthrope as a figure of fun, either by exposing him to direct ridicule, or by associating him physically or metaphorically with the figure of the Renaissance Fool. The third chapter introduces two non-Shakespearean stage misanthropes, Bohan from Greene's James IV, and the protagonist of the anonymous Timon Play, and examines the difficulties surrounding their presentation. In the fourth chapter I discuss Shakespeare's use of misanthropy as a character trait in several figures who are not themselves misanthropes. Chapter five and six deal with two Shakespearean comic misanthropes, Jaques from As You Like It and Thersites from Troilus and Cressida, and examine the ways in which Shakespeare has surmounted the theatrical problems outlined earlier. Finally, I offer a detailed study of Timon of Athens, to show how Shakespeare attempts to build up sympathy for Timon in the first three: acts through this behaviour of the Athenians, the comments of Flavius and Apemantus, and the Alcibiades subplot; and then counts on this buildup of sympathy to carry through to the end of the play. I conclude, however, that for all its subtlety cf construction, Timon of Athens fails as a tragedy, primarily because of the intransigence of its subject matter. I believe that my approach should prove useful to a more detailed understanding of the play's dramatic structure.
Keywords: shakespeare; misanthropy; study; Appalachian Studies; English Language and Literature; Appalachian Studies